Karakteristik Batubara Beda Kualitas Berdasarkan Analisis Statistik Dasar di PT. Budi Gema Gempita, Merapi Timur, Lahat, Sumatera Selatan - Ria Novi Mayang Sari; Adree Octova (Departemen Teknik Pertambangan FT UNP, 2021)
Abstract. Pt. Budi Gema Gempita (PT. BGG) is one of the companies engaged in coal mining. Pt. BGG has 4 types of coal that will be done blending process where the coal has different quality based on seam. Seam 10A, 10B, 6A and 6A1 with calorie values of 5073 kcal/kg, 5259 kcal/kg, 6248 kcal/kg and 6110 kcal/kg. The problem that arises from the quality of coal is the difference in the caloric value of coal each time it is tested, either samples in the same location or at different locations. Factors that influence the decline in coal quality are contamination from coal filttor material, coal hauling activities, fine coal, une uniform grain size and weather and climate. From the calculation results obtained a graph of the relationship of influence between the parameters of coal quality and the value of calories that is the relationship between TM and CV, ASH with CV and TS with CV looks linear line that shows a negative relationship, meaning that if the value of TM, ASH and TS is high then the value of calories will decrease. The relationship between VM and CV and FC with CV looks linear line that shows positive relationship, meaning if the value of VM and FC is high then the caloric value will be high as well.Keywords: Basic statistics, coal quality, quality control, front, stockpile